Doodly-Based Multimedia Instructional Intervention and Academic Achievement of Undergraduate Students with Learning Disabilities in Educational Technology - Johnson, Idorenyin Edet; Ekwok, Lawrence Nkpang; Achua, Glory Augustine; Igajah, Mayen Ndaro; Tawo, Catherine Nyong; Akpa-Inyang, Francis Fabian (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
Traditional instructional strategies may not provide the essential elements necessary for students with learning disabilities (LDs) to learn effectively. This ultimately leads to decreased motivation and underachievement. Since Doodly-based multimedia has been scientifically proven to enhance learning outcomes, one wonders if such effects could be replicated on the academic achievement of students with LDs. The study explored the impact of Doodly-based multimedia instructional intervention (DBMII) on the academic achievement of undergraduate students with LDs in Educational Technology (EdTech). The research employed a 2x2 quasi-experimental factorial design, with pre- and post-tests to explore the effects of DBMII. The census sampling technique was used to draw a sample of 38 (22 males and 16 females) third-year special education students with confirmed cases of LDs. The data collection used the Educational Technology Achievement Test (ETAT). The validation was conducted by three specialists and had a reliability coefficient of 0.82 using the Kuder-Richardson 21 formula, before it was administered, marked, scored, coded, and analyzed. Analysis of Co-Variance (ANCOVA) was employed to test the hypotheses, setting the significance threshold at the 0.05 level. The findings revealed a statistically significant beneficial effect of DBMII on the academic achievement of undergraduate students with learning disabilities in EdTech. Also, gender did not significantly influence educational achievement, and no interaction effects between gender and Doodly-based multimedia instructions were observed. It was concluded that Doodly-based multimedia instructions have a statistically significant beneficial effect on the academic achievement of undergraduate students with LDs in EdTech, without any significant influence of gender.